PENGGUNAAN TANGGA PANEN LADA PORTABLE UNTUK MENGURANGI BEBAN KERJA DAN RISIKO CEDERA PADA PETANI LADA MELALUI METODE REBA DAN QFD - Prima, Febri; Prawatya, Yopa Eka; Khairunisa, Aminah; Aulia, Yayang; Hermawan, Yuda (Teknik Industri Unikom, 2024)
The development of a portable ladder for pepper harvesting in Sanatap Village, Sajingan Besar Sub-district aims to improve farmers' ergonomics, safety, and productivity. Using the Quality Function Rapid Entire Body Assessment (REBA) dan Deployment (QFD) methods, this study identified farmers' key needs such as ease of operation, lightweight materials, and ease of storage. The designed ladder is foldable, has wheels, and is made of strong yet lightweight galvanised iron, and has additional safety features. The results of the analysis showed a significant improvement in the farmers' working posture and a reduction in the risk of injury, from moderate risk (REBA score 4-7) to low risk (REBA score 2-3). This shows that the ladder can reduce the risk of injury to pepper farmers. In addition, this portable ladder is expected to not only improve the efficiency and safety of pepper farmers, but also open new business opportunities that contribute positively to the local economy. The implementation of this tool is expected to improve the welfare of farmers in Sajingan Besar Sub-district and provide practical solutions that are profitable and sustainable.